2012
DOI: 10.3390/rel3041103
|View full text |Cite
|
Sign up to set email alerts
|

Priesthood Satisfaction and the Challenges Priests Face: A Case Study of a Rural Diocese in the Philippines

Abstract: This article draws from the experience of Catholic priests based in a rural diocese in the Philippines. It will be argued that their satisfaction as diocesan priests is best understood as a religious emotion in spite of the challenges they face on a daily basis. Their challenges revolve around economic limitation, problems with their bishop and leaders, and relational isolation brought about by social and geographic distance. In spite of these challenges, priest-respondents have asserted that they are satisfie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Finally, the present study shows that there is a significant correlation between spirituality and priestly commitment. This result is consistent with previous studies that have shown that by having a close relationship with God, priests remain faithful in their priestly commitment (Cornelio 2012;Sunardi 2014).…”
Section: Correlations Among Spirituality Social Support and Priestlsupporting
confidence: 93%
See 4 more Smart Citations
“…Finally, the present study shows that there is a significant correlation between spirituality and priestly commitment. This result is consistent with previous studies that have shown that by having a close relationship with God, priests remain faithful in their priestly commitment (Cornelio 2012;Sunardi 2014).…”
Section: Correlations Among Spirituality Social Support and Priestlsupporting
confidence: 93%
“…It seems that through the support of companionship, a sense of belonging is very meaningful among Catholic priests. These results corroborate previous studies (Cornelio 2012;Hoge et al 1995;Virginia 1998;Zickar et al 2008) that have highlighted the importance of social support in the priestly life and ministry.…”
Section: Multidimensional Social Support For Priestssupporting
confidence: 92%
See 3 more Smart Citations